Defending Against Medical Error: Personal Reflections on the Legacy of John Senders - Sellen, Abigail (Sage, 2021)
Objective To honor the legacy of John Senders, a distinguished member of the Human Factors and Ergonomics Society, by a short, personal history of him, but then to honor his legacy by extending it through our own professional opinions, with an emphasis on the study of human error and its implications for healthcare systems—two topics in which he excelled. Background The authors are familiar with the topic and subject matter. One was a friend of Senders for over 50 years. Another was a collaborator and joint author with Senders (as well as his stepdaughter). All three authors have extensive publications in the topic areas. Method, Results, and Conclusion The authors used personal accounts of interactions with Senders at conferences, experiences living and working with him, and a brief review of his most personal, notable publications in healthcare. The reflections indicate a strong resonance on Senders’ contributions to system design that are relevant today in healthcare’s most challenging period in its history.